The Tenth Planetary Boundary To What Extent Energy Constraints Matter - Casazza, Marco; Liu, Gengyuan; Ulgiati, Sergio (Journal of Environmental Accounting and Management, 2026)
This paper introduces the energy constraints as the tenth existing Planetary Boundary (PB hereafter) for defining a safe operating space for humanity on Earth. Energy limitations, in fact, follow all the technical requirements, that are applied to all the existing PBs. After discussing about the specific power both of some planetary components and of some elements of the biosphere, the evolution of human civilization is discussed, considering its additive specific power. This is done in order to show the existing power shift originated by the industrialization and, subsequently, within the Anthropocene. The historical trend of Total Primary Energy Supply (TPES) for human civilization, expressed in terms of power and measured in units of [W], follow within the discussion. Consequently, both a lower preliminary limit (identified with the preindustrial TPES, according to the PB framework), and an upper threshold are identified. The latter is related to the total appropriation of the Net Primary Production (NPP). Finally, the foreseen TPES for the year 2050 is discussed under three different scenarios. Different “quality” goals are defined, according to different existing low-carbon scenarios, which are related to a sufficiency perspective for humanity. Such a transition is of paramount importance since it will enable humanity to remain into a safe operating space within the biosphere. While the paths to reach such an objective go beyond the scope of this paper, it is anyway remarked that both a socio-economic transition and policy efforts are necessary in order to involve the population by means of well-planned bottom-up actions.